Serum Albumin Level Can Predict Immunotherapy Response of Neuromyelitis Optica Spectrum Disorders in the Acute Phase - Xiang W; Wu Y; Li H; Zhu D; Yao X; Ding J; Wang Z; Guan Y (Journal of Inflammation Research, 2024)
Weiwei Xiang,1,* Yifan Wu,2,* Hongyan Li,1,* Desheng Zhu,1 Xiaoying Yao,1 Jie Ding,1 Ze Wang,1 Yangtai Guan1 1Department of Neurology, Ren Ji Hospital, Shanghai Jiao Tong University School of Medicine, Shanghai, People’s Republic of China; 2Department of Neurology, Xuanwu Hospital, Capital Medical University, Beijing, People’s Republic of China*These authors contributed equally to this workCorrespondence: Yangtai Guan, Department of Neurology, Ren Ji Hospital, Shanghai Jiao Tong University School of Medicine, No. 160, Pujian Road, Shanghai, People’s Republic of China, Email yangtaiguan@sina.comBackground: Neuromyelitis optica spectrum disorder (NMOSD) is an autoimmune demyelinating disease of the central nervous system. However, few biomarkers have been found to predict the outcome of immunotherapy. We investigated the relationship between the serum albumin (S-Alb) and response to immunotherapy in acute NMOSD patients.Methods: A total of 107 consecutive Chinese patients with acute NMOSD diagnosed between January 2013 and January 2022 were included in our prospective observational study. S-Alb was measured by the use of bromocresol green and immunoturbidimetric methods on admission. The immunotherapy response was assessed by the percentage change in the expanded disability status scale (EDSS) score from admission to discharge after treatment. We evaluated the association between S-Alb and immunotherapy response through multivariate logistic regression analysis.Results: S-Alb levels were significantly lower in patients who were resistant to immunotherapy than in those who were responsive to treatment (p< 0.001). S-Alb levels were positively related to a favorable response to immunotherapy (r=0.386, p< 0.001). The odds ratio (95% CI) for the association between S-Alb level and response to immunotherapy was 1.27 (95% CI=1.08, 1.50; p=0.004) after adjusting for potential factors. ROC analysis showed that patients with S-Alb levels lower than 40.85 g/L were likely to be resistant to immunotherapy.Conclusion: Our study indicated that a higher S-Alb was an independent indicator of response to immunotherapy in acute NMOSD patients.Keywords: immune diseases, NMOSD, immunotherapy, albumin, multivariate analysis